Application of probabilistic inference in defining impact of the general government sector's size on the economy and determining the size of the sector by the economy in the EU - Teresa Mroczek; Tomasz Skica; Jacek Rodzinka (e-Finanse: Financial Internet Quarterly, 2018)
The article's objective is to apply probabilistic inference in determination of the impact of the size of the general government sector on the economy and the impact of the economy on the size of the sector in EU Member States. The research indicated that 4 of 13 variables describing the size of the general government sector have a significant impact on the economic parameters and determined their value and that impact of the economy on the general government sector is significantly more identified than determination of the economy by the sector size.
Keywords: E62; H11; H20; H50; H60; 330; General government sector size; economy; public finance; impact of size of general government sector on the economy; Bayesian networks; probabilistic inference